Fixed-Circle And Fixed-Disc Problem In Metric Spaces - Chandra, Vineeta; Patel, Uma Devi (Vojnotehnički glasnik / Military Technical Courier, 2025)
In this paper, we give certain existence theorems using different type of contraction for fixed circles and fixed disc results of self-mapping on metric spaces. Also, we give some necessary examples to show the validity of our theoretical results.